Alcohol Consumption Among Inflammatory Rheumatic Patients: A Survey From Turkey - H. Fatih ÇAY,; Özge İLLEEZ,; Hilal KOCABAŞ,; İlhan SEZER,; Ece KAPTANOĞLU,; Cahit KAÇAR5, (Archives of Rheumatology, 2012)
Objectives: In this study, we aimed to evaluate alcohol consumption of Turkish rheumatic patients. Patients and methods: A total of 332 subjects [185 males and 147 females; mean ages of 41.2 (95% CI 39.5- 43.0) and 45.2 (95% CI 43.4-47.1) years, respectively] with rheumatoid arthritis (RA), ankylosing spondylitis (AS) and healthy controls were questioned regarding their alcohol habits. Alcohol consumers were asked to fill out the Turkish version of the Michigan Alcoholism Screening Test (MAST). Results: A total of 37.3% of all subjects were alcohol consumers. Nearly 50% of males and 20% of females drank alcohol. Rheumatoid arthritis group had the lowest rate of alcohol consumption (23.0%), while healthy controls had the highest rate (45.6%). The mean MAST scores were 3.02 (95% CI: 2.36-3.69) and 3.13 (95% CI: 1.76-4.5) for the AS and RA groups, respectively, indicating statistically lower rate compared to the healthy controls [4.94 (95% CI: 4.14-5.73) (p<0.001)]. An analysis of the MAST scores by categories revealed that most of the alcohol abusers / alcoholics were in the healthy control group. Conclusion: Our results showed that alcohol consumption, an important public health problem, has not been regarded as a major issue for the patients with rheumatic diseases. Further studies are required to evaluate the potential factors which may play a role in the alcohol consumption habits of rheumatic patients.